A Semantic Study of the Word Goodness in the Holy Qur’an: Surah Al-Baqarah as an Example - Thamer Al-Hamdani, Warda Mezer (Journal of Tikrit University for Humanities, 2024)
The examination of the word "goodness" as presented by God in Surat Al-Baqarah, a surah of the Qur’an, is a significant subject in semantic research that has caught the attention of experts. This study a has significant importance within the field of language studies. The term "goodness" is often used in many surahs of the Holy Qur’an, including Surat Al-Baqarah. It is found in twenty-seven words over twenty-one verses in Surat Al-Baqarah, and its origin may be traced back to the meter. The hamza was removed due to its ultimate origin and its usage as a substitute for lighting, since it is mostly utilized as a kind of preference. The use of hamza in it has a limited history, but its removal has been widely practiced. There is no distinction between feminine and masculine forms when it comes to expressing preference. Both individuals express a positive sentiment. The purpose for selecting this subject is to ascertain the meanings associated with the term "goodness" and its many classifications. Goodness can be attributed to various factors, such as the virtue of fasting, the significance of wealth, the concept of rewards, and the significance of revelation. This text aims to elucidate the meaning of each type of goodness and provide an introduction to each, supported by Qur’anic verses. The investigation culminated in the identification of the most significant findings, as well as a compilation of the authorized sources and references used in the study.